Anglo-Saxon lead from the Peak District: where does it lead?: a new approach to sourcing Anglo-Saxon lead - Wright, Paul (2018)
A new methodology has been developed , which uses tin as a marker for recycled Roman lead. Analysis of lead artefacts show that along the Derwent/ Trent/ Humber corridor recycled lead was continuing in use in the 5th-7th centuries, and plentiful fresh lead first appears in the record in the 9th century with no tin. There is a widespread gap in lead artefacts from the 8th century, which implies that recycled had been exhausted. The main source of Anglo-Saxon lead in this region is probably the Derbyshire Peak District, but some lead from window cames may have alternative sources, suggesting itinerant glaziers. The analytical methods were chosen for the relatively large size of the sample chambers, enabling surface analysis of the artefact with no damage.